(untitled) (The Macau Ricci Institute Journal, 2020)
The appeals by Pope Francis to safeguard the future of our planet by furthering peace between and within countries, and to maintain the natural environment are most important. They should serve as a guideline to future economics. Our three key ideas have one common background: Appeals and admonitions, while necessary, are not sufficient. What is needed are institutional conditions that give people the possibility and the incentives to develop innovative and unorthodox ideas, and to act in the directions desired. We propose three institutions for change. All three are based on ideas and rules that are, or were, used in the Catholic Church.